(3efXheI aj Md GdeCchdGJ hGdCWYeIs - (3CMeO Hf YeGO Hf jhSa Hf YHO GdfHj, CHh GdYHGS, TgGH GdOjf GdCbagSj Ke GdbGgQj , GHf GdpYneGO ,J (B808 (3g` s ((3SdjeGf Hf eMeO Hf SMdhd GdEOdHi s)
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje hHg CSJYjf GdMeO ddg Ydi GdfYje MeOkG jhGai fYeI GdQMje adceG ai CQVg eHGM EdG GdPi NUg GdLfGM s
(3BNQgG (B:s
(3ajbJfi GdNfRjQ hGdcdGHG dCLd RGO aGage GdLhGHG hGdMeO ddg GdPi Hg JJe GdUGdMGJ hHg GdfXe NJe JeJ gPg GdCHjGJ HMeO ddg hYhfg hMSf Jhajbg s
(3HgG fXGe GdJYbjHIs
(3efXheIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B184 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B26s
Keywords: (3Gdabg GdESdGejs